Mormyroidea-inspired electronic skin for active non-contact three-dimensional tracking and sensing - Zhou, Jingkun; Li, Jian; Jia, Huiling; Yao, Kuanming; Jia, Shengxin; Li, Jiyu; Zhao, Guangyao; Yiu, Chun Ki; Gao, Zhan; Li, Dengfeng; Zhang, Binbin; Huang, Ya; et al. (Nature communications, 2024)
The capacity to discern and locate positions in three-dimensional space is crucial for human-machine interfaces and robotic perception. However, current soft electronics can only obtain two-dimensional spatial locations through physical contact. In this study, we report a non-contact position targeting concept enabled by transparent and thin soft electronic skin (E-skin) with three-dimensional sensing capabilities. Inspired by the active electrosensation of mormyroidea fish, this E-skin actively ascertains the 3D positions of targeted objects in a contactless manner and can wirelessly convey the corresponding positions to other devices in real-time. Consequently, this E-skin readily enables interaction with machines, i.e., manipulating virtual objects, controlling robotic arms, and drones in either virtual or actual 3D space. Additionally, it can be integrated with robots to provide them with 3D situational awareness for perceiving their surroundings, avoiding obstacles, or tracking targets. Developing electronic skins for sensing the spatial location of objects beyond two-dimensional space is difficult. The authors present a flexible, lightweight, and transparent electronic skin for non-contact accurate 3D motion sensing. This achieves micron-level precision, reducing complexity and power consumption.